Reconstruction and reinterpretation as post-secular bricolage phenomena - Konstantin Gipp (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2023)
The article is devoted to the analysis of the mechanisms of formation of modern religious post-secular consciousness. The principal feature of this consciousness is the combination of religious and secular elements, which creates, according to the apt expression of the religious scholar Dm. Uzlaner, post-secular hybrids. It seems that the main mechanism for creating such hybrids is bricolage. Post-secular bricolage manifests itself in the phenomena of reconstruction and reinterpretation. The process of reconstruction is necessarily involved in the fixation and rationalization of religious tradition and has two components. Firstly, it is an appeal to the remnants of tradition preserved in folk beliefs and practices, and secondly, it is the use of materials of scientific ethnographic research, both conducted in the previous period and modern ones. The result of this process is the emergence of "neotradition", when the reconstruction of lost and forgotten practices based on scientific approaches leads to the emergence of post-secular hybrids, where the religious form of the recreated phenomena is combined with the secular goals of this activity and the secular understanding of their content. There is also reflection, comprehension of traditional beliefs, a certain theology of tradition is created, but in the process of this, concepts of secular scientific (or paranientific) language are often used, applied according to the principle of "everything will do", i.e., according to the principle of bricolage. Reinterpretation affects tradition more deeply. During reinterpretation, such a transformation of the religious system occurs, in which the primary system remains in the final product of the process as an element, and the original system is radically rethought, the product of reinterpretation is not completed, it is open for further changes. The reinterpretation product can also be characterized as a post-secular hybrid. Our proposed analysis of the features of the functioning of the mechanism of intellectual bricolage in the post-secular era, consideration of the phenomena of reconstruction and reinterpretation in this perspective gives, in our opinion, new tools for studying the processes of formation of modern religious consciousness. The conclusions of the article, in addition to the analysis of published studies of the modern religiosity of the peoples of the Russian Federation, are also based on field studies conducted by us since 2013 in the Nenets, Yamalo-Nenets Autonomous District and some other regions of the Russian Federation.